Mecanismo para superação das barreiras na implantação da produção mais limpa em pequenas e médias empresas: estudo de múltiplos casos no setor metalúrgico - Leite, Roberto Rodrigues (2014)
Clean Production is an interesting approach to be applied in Small and Medium Enterprises of metallurgical branch because offers viable alternatives for improvements in their manufacturing processes enabling economic and environmental gains. It introduces herself as a prevention strategy to risks of environmental impacts while providing increased process efficiency, improving the quality of products and services. Unfortunately Small and Medium Enterprises make little use of this tool, using as alternative the final treatment of tube. Even Brazilian law characterizing the generator as responsible for disposal of their waste, lack of information and ignorance about the alternatives the available for this purpose causes little attention for given this responsibility by the companies, which may result from deficiency in supervision or in the belief that actions directed at preserving the environment entail in high costs. This study presents the results of work carried out with four Small and Medium Enterprises of the metal industry with the goal of developing a mechanism for identifying and overcoming barriers to implementation of Cleaner Production, considering the economic and environmental assessment as a major factor for decision making. In particular, was held a bibliographic and bibliometric study on the subject, we identified the barriers, we analyzed its causes and effects in order to find alternatives to overcome them. The technique adopted for data collection was interviews and observation, enabling compose a study of multiple cases. The mechanism for identifying and overcoming barriers to implementation of Cleaner Production was applied in four companies enabling understand that, with the determination of the effects caused by the barriers becomes possible to identify alternative solutions to overcome, and if a company decides to implement the Cleaner Production, can get significant economic gain and reduce their environmental impacts.